2022
DOI: 10.21203/rs.3.rs-1321383/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactive Effects of Melatonin and Salicylic Acid on Brassica Napus Under Drought Condition

Abstract: Aims Understanding the interactive actions of melatonin and salicylic acid in counteracting the negative effects of drought is imperative for increasing growth and yield of canola. Here we discuss the interactive effects of exogenously applied melatonin (MET) and salicylic acid (SA) on morphology, physiology, and biochemical characteristics of drought stressed canola plants. Methods Two cultivars of canola (Super canola and Faisal canola) were used. MET (0.1µM) and SA (0.50mM) were applied in two ways, i.e.,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As it is known, if the plant height is getting higher, it increases surface evaporation and also the loss of water. Similarly, several researchers reported that drought stress has inhibitory effects on plant growth and decreases the shoot and root fresh weight (Sattar et al, 2021, Rafique et al, 2022. Water deficit decreased seed GR and seed germination percentage.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As it is known, if the plant height is getting higher, it increases surface evaporation and also the loss of water. Similarly, several researchers reported that drought stress has inhibitory effects on plant growth and decreases the shoot and root fresh weight (Sattar et al, 2021, Rafique et al, 2022. Water deficit decreased seed GR and seed germination percentage.…”
Section: Resultsmentioning
confidence: 84%
“…It is estimated that the world population, which was about seven billion in recent years, will reach nine billion by 2050, and to support such a population, food security is more threatened by different kinds of environmental stresses (Khan et al, 2020). In recent years, with the effect of global warming, being an environmental problem, the importance of water has begun to be felt with agricultural drought (Khanna-Chopra and Selote, 2017;Rafique et al, 2022).…”
Section: Introductionmentioning
confidence: 99%